The effects of the Nordic hamstring exercise on sprint performance and eccentric knee flexor strength: A systematic review and meta-analysis of intervention studies among team sport players - Bautista, I. J.; Vicente-Mampel, J.; Baraja-Vegas, L.; Segarra, V.; Martín, F.; Van Hooren, B. (Journal of Science and Medicine in Sport, 2021)
Objectives: The primary aim of this study was to investigate the effects of the Nordic hamstring exercise (NHE) on sprint performance (i.e., 5, 10 and 20 m) and explore associations between study characteristics and sprint outcomes in team sport players. Secondary aims were to (1) investigate the effects of the NHE on eccentric strength of the knee flexors (ESKF) with categorical subgroup analysis to determine differences between recreationally, well-trained individuals and young athletes, (2) determine the relation between ESKF and sprint performance in team sport players, and (3) explore the effect of study characteristics (i.e., weekly volume, time duration and body mass) on ESKF. Methods: Electronic databases were searched until the 20th of June 2020. 17 studies met the inclusion criteria. Random-effects meta-analyses were used to determine the mean difference (MD) or standardized change of mean difference (SCMD) between NHE and control group for sprint time and ESKF, respectively. Results: NHE interventions showed a positive effect on sprint performance (-0.04 s [-0.08, -0.01]). Sub-group meta-analyses indicated no significant differences in 5 and 20 m sprint performance (MDsprint(5m) = -0.02 s [-0.10, 0.06]) and (MD sprint(20m) = -0.05 s [-0.30, 0.19]), respectively. A significant difference was however found for 10 m sprint performance (MDsprint(10m) = -0.06 s [-0.10, -0.01]). Meta-analysis on the effects of the NHE on ESKF showed a significant benefit of 0.83 SCMD [0.55, 1.12] in favour of the intervention group. Conclusions: Studies with some concerns or high risk of bias show that training programs involving the NHE can have small beneficial effects on sprint performance in team sport players. Studies with some concerns or high risk of bias showed moderate beneficial effects on ESKF among a sample of relatively untrained individuals. However, for well-trained team sport players, the improvements in ESKF were less consistent, suggesting a higher training intensity during the NHE may be required to induce adaptations.